THE IMPACT OF TASK-BASED LEARNING ON SPEAKING FLUENCY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In recent decades, the primary focus of language teaching has shifted from grammar-based instruction to communicative and learner-centered methodologies. One such influential approach is Task-Based Learning (TBL), which places real-life communication tasks at the core of the instructional process rather than traditional teacher-led explanations. Speaking fluency, as one of the central objectives of communicative language competence, remains one of the most challenging skills for learners to develop. Many learners, despite years of learning English, still struggle to express their ideas smoothly, with confidence, and without frequent hesitation. Therefore, examining how Task-Based Learning influences speaking fluency is essential for understanding its practical value in contemporary English as a Foreign Language (EFL) classroom.